Odpowiedzi

Najlepsza Odpowiedź!
2009-12-03T22:59:48+01:00
I1* 11-I2*4-I3*5=5
I2*15-I1*4-I3*5= -10
I3*16-I1*5-I2*5=0→I2*5=I3*16-I1*5→I2=I3*16/5-I1

I1* 11-(I3*16/5-I1)*4-I3*5=5
(I3*16-I1*5)*3-I1*4-I3*5= -10

I1* 11-I3*64/5+I1*4-I3*5=5
I3*48-I1*15-I1*4-I3*5= -10

I1* 15-I3*89/5=5 / *19
I3*43-I1*19= -10 /*15

I1* 285-I3*1691/5=95
I3*645-I1*285= -150
------------------------
I3*645-I3*1691/5=-55 /*5
I3*3225-I3*1691=-275
I3*1534=-275
I3= - 275/1534

nie wiem czy wspłczynniki nie pomyliłeś, bo taki wynik dziwny.
Teraz podstaw I3 do równania I3*43-I1*19= -10 , a potem do I2=I3*16/5-I1






1 5 1